The oldest evidence of calcific myonecrosis?. (16th January 2018) - Jerković, I.; Kružić, I.; Bašić, Ž.; Mihanović, F.; Anđelinović, Š.
Abstract: On the archaeological site on the necropolis of the Ancient Salona, skeletal remains of 25–34 years old male were found. On the left lower leg, there were extensive pathological changes that were manifested on tibia and fibula as thickening of the bone shafts and fusion of these bones by calcified fusiform mass. The bone borders were sharpened with a new lighter layer of bone, enthesophytes, and/or with calcified tissue that merged with bone. Also, laminar bony outgrowths/plaques were visible on the bone surfaces. Periosteal reaction was visible on the right ulna, femora, and tibiae. Upon differential diagnosis, on the basis of the affected compartment and the type of the ossification, we have concluded that it was very probably a case of a calcific myonecrosis. However, due to lack of clinical data that are almost never available in ancient skeletons, we could not determine what had caused the condition. As it was to our knowledge the oldest finding of the disease and also the first one that describes pathology on the dry bone specimen, we believe that this case study will contribute both to the study of the antiquity of disease as well as to its manifestations on dry bones.